THE INFLUENCE OF ILLUMINATION WITH THE METHOD DEMONSTRATIONS AGAINST THE ABILITY OF THE FAMILY IN DOING MASSAGE OXYTOCIN ON BREASTFEEDING IN BPM HJ. UMI SALAMAH PETERONGAN JOMBANG - Widowati, Haksari; Kusyani, Asri; Azizah Kn, Umi (LPPM STIKes Bahrul Ulum Jombang, 2016)
For breastfeeding mother, smoothness of breastfeeding is the most important thing to suit her baby's nutrient. Involvement of the family also can influence mother to not give breastfeeding and from interview result, many mother didn't give breastfeeding because of many works to do and production of breastfeeding is less. Purpose of this research is to know the ability of the husband to give oxytocin massage to breastfeeding mother. Research design used pre-experimental method by using one-group pretest-post design approaches. The population is the husband as many as 37 persons in BPM HJ.Umi Salamah, sampling technique and quota sampling got samples as many as 20 persons. Gathering data used observation papers, analyzing data used paired T test method by using standard significance (0,05). Result of the research was average score before counseling 6,05 and after counseling 66,57. Based on statistic test, there was effect of counsel mg by using demonstration menthol to ability of the family (husband) in giving oxytocin massage as many as P= 0,000 (p<0,05) Effort to make breastfeeding run well is by giving oxytocin massage, by counseling and a/so demonstrating about oxyntic massage. This result was expected that family can apply and do that to the mother, there for Mather can give breastfeeding exclusively. Key Word: ASI (Breastfeeding), Oxytocin Massage, Counseling.